The Relationship Between Traffic Characteristics on Road Segments in Commercial Areas (Case Study: Basuki Rahmat Street, Palu City) - Hadi Parnanto Yunus; Taslim Bahar; Ratnasari Ramlan (International Journal Labs, 2026)
Commercial areas generate substantial traffic movements that influence traffic flow characteristics on urban roads. Basuki Rahmat Street in Palu City is one of the city's primary commercial corridors, experiencing increasing traffic activity that affects the relationships among traffic volume, speed, and density. This study aimed to analyze the relationships between traffic volume and speed, traffic volume and density, and speed and density, as well as to determine the most appropriate traffic flow model for Basuki Rahmat Street, Palu City. Traffic volume and speed data were collected through field surveys conducted during peak periods and were analyzed using the Greenshields, Greenberg, and Underwood traffic flow models. Road performance was evaluated in accordance with the Indonesian Road Capacity Guidelines (Pedoman Kapasitas Jalan Indonesia [PKJI]) 2023 using road capacity, degree of saturation, and Level of Service (LOS) indicators. The results indicated that the peak traffic volume reached 1,015 passenger car units (pcu)/hour, while the road capacity was 5,630.4 pcu/hour, with a degree of saturation of 0.18, corresponding to Level of Service (LOS) B, which indicates stable traffic flow conditions. The analysis of traffic flow characteristics showed that increases in traffic volume and density resulted in a reduction in vehicle speed. Among the three traffic flow models evaluated, the Greenshields model provided the closest representation of the observed traffic conditions and the PKJI 2023 parameters, with a maximum traffic volume of 1,505.51 pcu/hour, an optimum speed of 57.96 km/h, and a traffic density of 28.98 pcu/km. Therefore, the Greenshields model was identified as the most appropriate model for describing the traffic flow characteristics of the commercial corridor along Basuki Rahmat Street, Palu City.